2001
DOI: 10.1089/108729101300003645
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Vertically HIV-1–Infected Long-Surviving Children

Abstract: This study describes the clinical, immunologic, and virological characteristics of 30 vertically human immunodeficiency virus type 1 (HIV-1)-infected children older than 8 years of age (long-survivors) before the introduction of protease inhibitors therapy. All of them were followed from birth. At the age of 8 years, 7 children presented no HIV-1-associated signs or only mild ones and only 5 had severe clinical manifestations (acquired immune deficiency virus [AIDS]). The remaining 18 children presented modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The progression of HIV infection is different in pediatric patients than in HIV+ adult patient. In spite of some confusion and overlapping definitions of different pediatric HIV+ populations, it seems that HIV+/AIDS children have a bimodal progression of the disease: fast progression and slow progression (3). HIV+/AIDS children that are fast progressors die before they are three years old, whereas slow progressor HIV+/AIDS children survive more than three years (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of HIV infection is different in pediatric patients than in HIV+ adult patient. In spite of some confusion and overlapping definitions of different pediatric HIV+ populations, it seems that HIV+/AIDS children have a bimodal progression of the disease: fast progression and slow progression (3). HIV+/AIDS children that are fast progressors die before they are three years old, whereas slow progressor HIV+/AIDS children survive more than three years (3).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of some confusion and overlapping definitions of different pediatric HIV+ populations, it seems that HIV+/AIDS children have a bimodal progression of the disease: fast progression and slow progression (3). HIV+/AIDS children that are fast progressors die before they are three years old, whereas slow progressor HIV+/AIDS children survive more than three years (3). Protease inhibitors of HIV-1 introduced in the antiretroviral therapy against HIV in the middle of 90's and their later combination with inhibitors of transcriptase reverse established the highly active antiretroviral treatment (HAART).…”
Section: Introductionmentioning
confidence: 99%
“…Two retrospective studies of long-term survivors include descriptions of small subgroups of true nonprogressors. 7,8 Several additional studies have reported analyses of 1 or 2 virologic or host genetic variables in pediatric LTNPs. One report suggested that functional and structural alterations in HIV nef genes correlate with pediatric LTNPs.…”
mentioning
confidence: 99%
“…1 However, the mother-to-child transmission rate of HIV-2 is reduced about 10-to 20-fold compared to HIV-1. 2,3 Vertical transmission of HIV-2 has been molecularly proved only once. 4 Compared to HIV-1, the epidemiology of HIV-2 is more difficult to study because most infections are diagnosed many years after infection has occurred.…”
mentioning
confidence: 99%